Introduction to the Special Issue on Clostridioides difficile - Guido Granata; Davide Roberto Donno (MDPI AG, 2021)
The Gram-positive, anaerobic bacterium Clostridioides difficile (CD) represents the most common cause of nosocomial diarrhea worldwide and is responsible for increased morbidity and mortality, and prolonged hospital stays [...]